Effect of post AI intrauterine treatment with E. coli lipopolysachharide and autologous serum on characteristics of cervico-vaginal mucous in subclinical endometritic cows - SINGLA, P; SINGH, JAGIR; DHALIWAL, G S; KUMAR, AJEET (The Indian Journal of Animal Reproduction, 2023)
Sub-clinical bacterial endometritis is a common cause of repeat-breeding in cows. The present study was conducted on 36 cows with confirmed sub-clinical endometritis. Based on the treatment protocol, these cows were divided randomly into three groups of 12 animals each. Group 1 (control}, Group 2 and 3 cows were infused intrauterine with 20 ml of phosphate buffer saline(PBS), E.coli lipopolysaccharide (LPS) IO0μg and E. coli LPS IO0μg + 5 ml of autologous serum, respectively, 8-12 hr after insemination. Cervico-vaginal mucus (CVM) was collected before artificial insemination (Al) and 12 hr after treatment. It was observed that colour and consistency of CVM became normal in significant number of animals. A significant decrease in pH of CVMwas also observed in treated animals.
Keywords: Lipopolysachharide; autologous serum; sub-clinical endometritis; cervico-vaginal mucus; cows